2019
DOI: 10.1177/0706743718802798
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Research Productivity among Academic Psychiatrists in Canada

Abstract: Objectives: Gender inequity in academic medicine persists despite increases in the number of women physicians. We sought to explore gender differences in research productivity for academic psychiatrists in Canada. Methods: In a cross-sectional study of the 3379 psychiatrists in all 17 university departments of psychiatry in Canada, research productivity, as measured by the h-index and number of publications, was compared between women and men using a negative log binomial regression model to generate relative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 41 publications
(66 reference statements)
1
17
0
1
Order By: Relevance
“…8,10,11,12,13,14,22,28,29 Some medical specialty–specific studies applied basic controls for a small number of author-level variables. 3,4,5,6,7 Second, using ICC articles as our outcome allowed us to study a particular type of solicited article for a large number of medical journals and with a large sample size. Third, to our knowledge, our study is the first to provide journal-specific estimates of gender disparities for a large number of medical journals using consistent methods alongside all-journal averages.…”
Section: Discussionmentioning
confidence: 99%
“…8,10,11,12,13,14,22,28,29 Some medical specialty–specific studies applied basic controls for a small number of author-level variables. 3,4,5,6,7 Second, using ICC articles as our outcome allowed us to study a particular type of solicited article for a large number of medical journals and with a large sample size. Third, to our knowledge, our study is the first to provide journal-specific estimates of gender disparities for a large number of medical journals using consistent methods alongside all-journal averages.…”
Section: Discussionmentioning
confidence: 99%
“…One study demonstrated that women continued to have fewer publications after adjusting for career duration (adjusted relative rate 0.46, 95% CI 0.39 to 0.55). 57 For h-index, 41 studies comparing 29 923 men to 12 286 women were included. Men had a higher h-index than women (mean difference 5.97, 95% CI 4.77 to 7.16, p<0.00001, I 2 =98%; online supplemental eFigure 9).…”
Section: Meta-analysis Of Secondary Outcomesmentioning
confidence: 99%
“…One study demonstrated that women continued to have a lower h-index after adjusting for career duration (adjusted relative rate 0.62, 95% CI 0.54 to 0.72). 57 For federal research funding, 21 studies comparing 87 205 men to 39 638 women were included. Men were 1.71 times more likely to hold a federal research grant (OR 1.71, 95% CI 1.41 to 2.08, p<0.00001, I 2 =88%; online supplemental eFigure 12).…”
Section: Meta-analysis Of Secondary Outcomesmentioning
confidence: 99%
“…A substantial body of work in social studies of science finds consistent evidence that women academics have lower publication rates and typically receive fewer citations per publication than men academics (Beaudry & Larivière, 2016;Cameron, White, & Gray, 2016;Chauvin, Mulsant et al, 2019;Ghiasi, Larivière, & Sugimoto, 2015;Larivière, Ni et al, 2013;Symonds, Gemmell et al, 2006;van Arensbergen, van der Weijden, & van den Besselaar, 2012). (I was unable to find any literature that reported findings for nonbinary, genderqueer, or transgender identities.…”
Section: Author Identificationmentioning
confidence: 99%
“…(I was unable to find any literature that reported findings for nonbinary, genderqueer, or transgender identities. Chauvin et al (2019) note that they "planned to include faculty identifying as nonbinary or genderqueer in a separate group," but "were unable to identify any such faculty from publicly available data sources.") To control for these gender effects, the online tool genderize.io was used to attribute gender to all authors based on their first or given name.…”
Section: Author Identificationmentioning
confidence: 99%